Identification of the monomeric composition of poly(styrene)acrylates - Yu. A. Yakovleva; N. A. Barykin; O. S. El'tsov (Chimica Techno Acta)
The work is devoted to qualitative analysis of poly(styrene)acrylates, the definition of the content of styrene in them. The methods of IR, NMR spectroscopy and gas chromatography-mass spectrometry were used for analysis. It was shown that the integrated use of modern spectral methods allows unambiguous to lead identification of the components in the copolymer and to use of spectral data for quantitative determinations.